2011
DOI: 10.1007/s00253-011-3591-x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate accumulation of metabolites results in a bottleneck for mineralisation of the herbicide metabolite 2,6-dichlorobenzamide (BAM) by Aminobacter spp.

Abstract: Degradation and mineralisation of the groundwater contaminant 2,6-dichloro-benzamide (BAM) was investigated in two Aminobacter strains focussing on the induction of BAM degradation and mineralisation and occurrence of intermediate metabolites. The BAM degradation rate was independent of whether the cells were pre-grown in the absence or presence of BAM, thus indicating that the first step in the degradation pathway was constitutively expressed. In contrast, (14)CO(2) production was stimulated when cells were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
(31 reference statements)
4
26
1
Order By: Relevance
“…Three times lower density resulted in 94 % degradation of 2.8 μg/L BAM (Table 3), giving that each cell in those filters then degraded on average~10 −12 μg BAM per min. Previous batch experiments with liquid pure cultures have shown that each MSH1 cell may degrade 10 −10 μg BAM per min at 20°C with a BAM concentration of 123 μg/L (Simonsen et al 2012). Only~1 % of this degradation rate was achieved in our filters, showing that it may be difficult to compare results from shaking flasks containing pure liquid cultures with those obtained from column studies.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Three times lower density resulted in 94 % degradation of 2.8 μg/L BAM (Table 3), giving that each cell in those filters then degraded on average~10 −12 μg BAM per min. Previous batch experiments with liquid pure cultures have shown that each MSH1 cell may degrade 10 −10 μg BAM per min at 20°C with a BAM concentration of 123 μg/L (Simonsen et al 2012). Only~1 % of this degradation rate was achieved in our filters, showing that it may be difficult to compare results from shaking flasks containing pure liquid cultures with those obtained from column studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, an additional degradation product not visible on UPLC-UV was visible and showed a 14 C activity of~3 % of the added 14 C-BAM in filters containing both old and "fresh" cells. This degradation product has previously been detected using TLC, but the exact structure is still not known, although it has been described as one or more very polar compounds formed after cleavage of the aromatic ring (Simonsen et al 2012). Approximately 17 % of the added 14 C-BAM was found as 14 C-HCO 3 − , representing a minimum mineralization, as losses of 14 CO 2 and incorporation into biomass could not be quantified.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…This pollution can impair water quality (1, 2) and lead to significant economic effects when pollutant concentrations warrant closure or mandated remediation of a contaminated drinking water source (3,4). Exploitation of microbial processes has long been considered an attractive option to remediate contaminated water resources (5).…”
mentioning
confidence: 99%